Quality of water for reprocessing of medical devices in healthcare facilities in Nepal - Gopal Panta; Ann K. Richardson; Ian C. Shaw (IWA Publishing, 2021)
Reusable medical devices are decontaminated and sterilized often many times by healthcare facilities across the globe. Reprocessing of medical devices comprises several processes and water plays an important role in some of these, including cleaning and steam sterilization. The water used is required to have certain qualities to ensure the effectiveness of the processes. In this short communication, we report findings of our study which measured quality parameters (pH, total hardness) for water used for medical device reprocessing in 13 primary and secondary care public hospitals in Nepal. The mean pH of water used for reprocessing of medical devices varied from 6.48 to 8.05 across the hospitals whereas the mean total hardness of water varied from 5.93 to 402.50 mg/L CaCO3. Although the range of the mean water pH across hospitals fell within the recommended range, many of the hospitals had mean total hardness higher than recommended for cleaning medical devices. None of the hospitals had mean total hardness suitable for using as feed-water for steam generation. Public hospitals in Nepal should have appropriate water treatment systems so that the recommended water quality can be achieved to ensure effective decontamination and reprocessing of medical devices. HIGHLIGHTS We have highlighted the crucial role of water in reprocessing of reusable medical devices.; This is the first ever study reporting quality parameters of water used for medical device reprocessing in public hospitals in Nepal.; Hospitals included in the study covered all geographical terrains in Nepal.; Recommendations have been made for treatment of water to ensure adequate reprocessing of medical devices.;